Rock fragmentation by blasting : proceedings of the 9th International Symposium on Rock Fragmentation by Blasting - Fragblast 9, Granada, Spain, 13-17 September 2009 /: proceedings of the 9th International Symposium on Rock Fragmentation by Blasting - Fragblast 9, Granada, Spain, 13-17 September 2009. ([2014?]) - Unknown
No abstract available